Impact of combinatorial immunotherapies in breast cancer: a systematic review and meta-analysis - Sisodiya, Sandeep; Kasherwal, Vishakha; Rani, Jyoti; Mishra, Neetu; Kumar, Sandeep; Khan, Asiya; Aftab, Mehreen; Shagufta,; Singh, Payal; Gupta, Ekta; Tanwar, Pranay; Hussain, Showket (Frontiers in Immunology, 2024)
Background Breast cancer has the highest mortality rate among all cancers affecting females worldwide. Several new effective therapeutic strategies are being developed to minimize the number of breast cancer-related deaths and improve the quality of life of breast cancer patients. However, resistance to conventional therapies in breast cancer patients remains a challenge which could be due to several reasons, including changes in the tumor microenvironment. Attention is being diverted towards minimizing the resistance, toxicity, and improving the affordability of therapeutics for better breast cancer management. This includes personalized medicine, target-specific drug delivery systems, combinational therapies and artificial intelligence based screening and disease prediction. Nowadays, researchers and clinicians are also exploring the use of combinatorial immunotherapies in breast cancer patients, which have shown encouraging results in terms of improved survival outcomes. This study attempts to analyze the role of combinational immunotherapies in breast cancer patients, and offer insights into their effectiveness in breast cancer management. Methodology We conducted a systematic review and meta-analysis for which we selected the randomized clinical trials (RCTs) focused on completed Phase I/II/III/IV clinical trials investigating combination immunotherapies for breast cancer. The analysis aimed to assess the efficacy of combination therapies in comparison to mono-therapies, focusing on overall survival (OS), and progression-free survival (PFS). Results We observed that, combination immunotherapies significantly (P<0.05) improved OS as compared to single-drug therapies in the Phase I with overall Risk ratio (RR) of 16.17 (CI 2.23,117.50), Phase II with an overall RR of 19.19 (CI 11.76,31.30) and for phase III overall RR 22.27 (CI 13.60,36.37). In the case of PFS, it was significant with RR: 12.35 (CI 2.14, 71.26) in Phase I RR 6.10 (CI 4.31, 8.64) in phase II, RR 8.95 (CI 6.09, 13.16) in phase III and RR 14.82 (CI 6.49, 33.82) in Phase IV of clinical trials. Conclusion The observed improvements in overall survival and progression-free survival suggest that combination immunotherapies could serve as a better approach to breast cancer management.